"Fishing" of heteropolyacids into carbonaceous seine via coking. Issue 96 (9th October 2015) - Sushkevich, Vitaly L.; Ivanova, Irina I.; Lancelot, Christine; Moldovan, Simona; Ersen, Ovidiu; Ordomsky, Vitaly V.
Abstract : Heteropolyacid has been encapsulated into a porous carbon matrix using controlled coking. The catalyst demonstrated unique stability toward leaching with high activity in the esterification reaction. Abstract : The carbon encapsulated tungstophosphoric acid was synthesized by the controlled coking during gas phase reaction of formaldehyde with isobutene. The as-made material showed unique stability toward leaching in the aqueous phase due to localization of HPA clusters inside the porous coke matrix with high activity in the esterification reaction.